Event Triggering Using Hand Gesture Using Open CV (International Journal of Engineering and Computer Science, 2017)
Gesture recognition and pattern recognition are advancing at an exponential rate in the passing years. Hand gesture recognition has been a fascinating research area. Hand gesture recognition system provides us a novel, natural, innovative user friendly way of communication with the computers. Gesture recognition has varied area of application including human computer interaction, sign language, game playing etc. Hand gesture recognition have enormous in human computer interaction and robotic machineries. Today interfaces between human and computer are mouse and keyboard are but in near future hand and eye gestures would replace it. Through this application we can identify the number of fingers of our hand. We can trigger on event using predefined gesture scenarios. Hand gesture recognition also provides a low cost interfaces device for interacting with objects in virtual environment using hand gestures. Keywords: Event triggering, Hand Gesture Recognition, OpenCV, HCI(Human Computer Intraction).